A Case of Ruptured Pancreaticoduodenal Artery Aneurysm with Portal Vein Obstruction Caused by Abdominal Hematoma and Abdominal Hematoma Causing Portal Vein Obstruction Treated by Combined Therapy - Eto, Ryotaro; Nojima, Hiroyuki; Takayashiki, Tsukasa; Takahashi, Makoto; Suzuki, Daisuke; Yoshitomi, Hideyuki; Ohtsuka, Masayuki (Nihon Fukubu Kyukyu Igakkai Zasshi (Journal of Abdominal Emergency Medicine), 2019)
A 41-year-old man with abdominal pain was referred to our hospital and was diagnosed as having portal vein obstruction caused by extramural compression by an abdominal tumor. Despite the anticoagulant treatment that the patient was initiated on, blood tests revealed a continued fall of the hemoglobin level, and multidetector-row computed tomography (MDCT) showed an increase in the size of the abdominal tumor, a pancreaticoduodenal artery aneurysm, and celiac axis compression syndrome. Based on the findings, we diagnosed the patient as having a large hematoma and performed transcatheter arterial embolization for treating the pancreaticoduodenal artery aneurysm, and then, surgical removal of the abdominal hematoma and portal vein thrombus. The patient was discharged on day 40 after the initial surgery. Follow-up MDCT showed steady portal venous flow 2 years after the surgery. Portal vein obstruction caused by an abdominal hematoma resulting from pancreaticoduodenal artery aneurysm is extremely rare.